THE INFLUENCE OF COMPASSION ON CHARACTER DEVELOPMENT: A STUDY ON THE CHARACTER OF THE CHILD IN STEPHEN CRANE’S SHORT STORY “A DARK BROWN DOG” - Silvia Hany Arnelyantoro; Dina Isnaini Hanifah; Nadiyah Rahmatul Ummah (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study explores the profound impact of compassion on the character development of the child in Stephen Crane's "A Dark Brown Dog," employing Adam Smith's framework from "The Theory of Moral Sentiments" (1759). Our analysis reveals a significant transformation in the child, driven by the emergence of empathy, from initial indifference to a deep sense of compassion towards the dog. Initially, the child views the dog with contempt and engages in aggressive behavior, reflecting a sense of superiority. However, as the child's empathy grows through witnessing the dog's sincere efforts to please, a pivotal change occurs. The child begins to recognize the dog's intrinsic worth, leading to protective and affectionate behavior. This empathy not only fosters a stronger emotional bond but also cultivates courage within the child. The child's newfound empathy drives him to defend the dog against familial mistreatment, demonstrating a significant moral and emotional growth. The study highlights the transformative power of empathy in developing compassion and bravery, showcasing how moral sentiments can profoundly shape character.